Analysis Effect of The Implementation Learning Media Snake and Ladders In Geography Learning at Senior High School Hang Tuah 2 Sidoarjo - Mawar Setya Ningrum; Nawang Widhyhasworo; Dini, Frisca; Rifai; Ahmad Imam Khairi (International Journal of Geography, Social, and Multicultural Education, 2025)
Abstract This study aims to analyze the effect of applying Snake and Ladders learning media on improving students' understanding of geography material in the 12th grade at Hang Tuah 2 High School Sidoarjo. The research method used is quasi-experimental with a pretest-posttest design. The sample consists of 21 students selected purposively. Data were obtained through pretest and posttest assessments to measure students' understanding before and after the application of the learning media. Data analysis was conducted using the paired t-test, with results showing a significant difference between the pretest and posttest scores. The average pretest score was 60.52, while the average posttest score increased to 78.24. The t-test results indicated a t-value of 5.42 with a p-value < 0.01, indicating that the application of Snake and Ladders learning media has a positive and significant effect on improving students' understanding. Therefore, this study recommends the use of innovative learning media like Snake and Ladders to enhance geography learning outcomes in schools Keywords: Learning media, Snake and Ladders, Geography, Paired t-test, Active learning